Analysis of pleural effusions using flow cytometry - (:unkn) unknown (My University, 1996)
Flow cytometry allows a rapid and accurate analysis of the cells in serous fluids. The aim of this study was to evaluate the use of flow cytometric analysis in malignant pleural effuions. 26 patients (13 females, 13 males; mean age 52 ± 19 years; range 16-82) were included in the study. 15 had malignant pleural effusions (7 adenocarcinoma, 2 lymphoma, 2 chronic myeloid leukemia, 1 ovarian carcinoma, 1 small cell lung carcinoma, 1 squamous cell lung carcinoma and empyema, and 1 malignant mesothelioma) with positive cytology. 2 had benign effusions associated with malignancy (1 squamous cell lung carcinoma and congestive heart failure, and 1 neuroblastoma and hypoproteinemia). 9 had benign effusions (3 tuberculosis, 1 congestive heart failure, 3 parapneumonic pleural effusion, 1 benign mesothelioma, and 1 pulmonary embolism). Flow cytometric analysis of pleural effusions revealed an increased DNA index in malignant effusions: 1.32 ± 0.44 versus 0.88 ± 0.23 in benign effusions (p < 0.04). The cell cycle distribution of cells such as G1/G0 and S in malignant effusions did not differ from that of benign pleural effusions; however G2+M increased significantly in malignant effusions (p < 0.03). Using analysis of mononuclear immunophenotyping, CD3+, CD4+, and CD8+ cells did not show any significant difference between the two groups. The lymphocyte activation marker CD38 was positive in 57.6 ± 11.5% of malignant fluid cells and 38.5 ± 6.2% of benign fluid cells (p < 0.04). The mean carcinoembryonic antigen levels in malignant and benign pleural effusions were 98.7 ± 157.3 and 0.9 ± 1.2 ng/ml, respectively (p < 0.03). In conclusion, the results of our study indicate that finding cells with an abnormal DNA content strongly supports the diagnosis of malignant pleural effusions. Additionally, mononuclear cell phenotypes have to be taken into consideration for malignant pleural effusions, particularly activated T cells. We recommend that flow cytometry should be performed if the cytology is equivocal. © 1996 S. Karger AG, Basel.
Keywords: DNA index; Flow cytometry; Mononuclear cell phenotyping; Pleural effusions